The Chumash world at European contact : power, trade, and feasting among complex hunter-gatherers - Gamble, Lynn H. (University of California Press, 2008)
The author weaves together multiple sources of evidence to re-create the tapestry of California's Chumash society. Drawing from archaeology, historical documents, and ethnography, she describes daily life in the mainland towns, focusing on Chumash culture, household organization, politics, economy, and warfare.